EDUCATION, POLITICAL CONNECTIONS, AND FIRM PERFORMANCE: EVIDENCE FROM GROWTH TRIANGLE COUNTRIES - Saputra, Irvan Pratama; Soewarno, Noorlailie (Assets: Jurnal Akuntansi dan Pendidikan, 2024)
ABSTRACT This research aims to understand better how education influences overall company performance in the "growth triangle" nations of Malaysia, Thailand, and Indonesia and how it fosters favorable political relations. Furthermore, we investigate how education contributes to the effectiveness of environmentally friendly corporate social responsibility (CSR) initiatives, sometimes called "Green CSR," and technological innovation in enhancing firm performance. This study covers annual data from 2012 to 2023 and uses a threshold autoregressive model. Our findings show that education level and work experience significantly influence employee performance. Firms that prioritize education, offer development opportunities, and provide training tend to have more productive teams. ABSTRAK Penelitian ini bertujuan untuk lebih memahami bagaimana pendidikan mempengaruhi kinerja perusahaan secara keseluruhan di negara-negara “segitiga pertumbuhan” di Malaysia, Thailand, dan Indonesia, serta bagaimana pendidikan dapat mendorong hubungan politik yang menguntungkan. Selain itu, kami menyelidiki bagaimana pendidikan berkontribusi terhadap keberhasilan inisiatif tanggung jawab sosial perusahaan (CSR) yang ramah lingkungan, yang kadang-kadang dikenal sebagai “CSR Hijau” dan bagaimana inovasi teknologi meningkatkan kinerja bisnis. Penelitian ini mencakup data tahunan dari tahun 2012 hingga 2023 dan menggunakan model autoregresif ambang batas. Temuan kami menunjukkan bahwa tingkat pendidikan dan pengalaman kerja secara signifikan mempengaruhi kinerja karyawan. Perusahaan yang memprioritaskan pendidikan, menawarkan kesempatan pengembangan dan memberikan pelatihan cenderung memiliki tim yang lebih produktif.